Genetic Variation Analysis of the E6 HPV 16 Gene Using RFLP In Silico - Annisa, Silvy; Rahmawati, Atika Ayu; Nadira; Khairani, Fidia Aura; Achyar, Afifatul (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2024)
Cervical cancer is cancer that attacks epithelial cells or the outer surface layer of the cervix. This cancer is most commonly caused by the high risk type of Human Papillomavirus. The RFLP method uses restriction enzymes to cut certain nucleotide sequences at specific positions that produce fragments of different lengths. The purpose of this study was to determine the polymorphism that occurs in the E6 gene of the HPV 16 virus. This research was conducted using RFLP in silico. Virtual descriptive methods are used to analyze data and collect information about the object of study. The restriction enzyme HpaII was used in this study. The results showed that there were two alleles (A1 and A2) out of a total of 15 sequences of the E6 HPV 16 gene in Popset 636528409 indicating that there was a genetic variation in the gene.